2017
DOI: 10.1093/sleep/zsx173
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing MSLT Specificity in Narcolepsy With Cataplexy

Abstract: A better characterization of R sleep by latency, duration, and sleep stage sequence facilitates detection of false positives and, hence, contributes to a higher MSLT specificity in NC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 32 publications
3
7
0
1
Order By: Relevance
“…These findings are in line with other published reports [12][13][14]. The specificity of MSLT could be increased by reducing mean sleep latency limit to 5 min and analyzing both the proportion of REM sleep in all the naps and the sequence of occurring sleep stages-whether REM sleep occurs before stage N2 sleep-but this would also reduce the sensitivity to around 50% [15,16]. A test-retest reliability of MSLT is also limited, especially in other diseases than NT1 [17].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with other published reports [12][13][14]. The specificity of MSLT could be increased by reducing mean sleep latency limit to 5 min and analyzing both the proportion of REM sleep in all the naps and the sequence of occurring sleep stages-whether REM sleep occurs before stage N2 sleep-but this would also reduce the sensitivity to around 50% [15,16]. A test-retest reliability of MSLT is also limited, especially in other diseases than NT1 [17].…”
Section: Discussionsupporting
confidence: 90%
“…One study examined the use of a fixed duration of nap trials on the MSLT findings but further research is needed on the impact of changes in nap duration on SOREMPS. 61 Data show that MSLT findings vary by age suggesting that age specific diagnostic criteria may need to be developed particularly for children and older adults. 19 Research on MWT results and their relationship to driving and workplace safety are needed and could potentially provide diagnostic and treatment cutoffs.…”
Section: Discussionmentioning
confidence: 98%
“…Insufficient sleep syndrome was the leading sleep diagnosis on re-evaluation in this patient cohort. The average TST of the cohort (404 min) by actigraphy was less than the AASM recommended adult sleep duration of 7-9 h, with several [10]. As noted previously, inadequate sleep duration is a significant problem in active duty military members with as many as 72% of soldiers reporting 6 or less hours of sleep per night [21].…”
Section: Discussionmentioning
confidence: 81%
“…A recent case series in three active duty service members suggested that misdiagnosis occurs in the military as well as civilian population [9]. SOREMPs, an essential diagnostic criterion for narcolepsy, have been noted in several other sleep disorders including OSA, circadian rhythm sleep-wake disorders, and insufficient sleep syndrome [10][11][12][13][14]. Therefore, judicious use of diagnostic tests is recommended including polysomnography (PSG) and actigraphy to evaluate for these confounding conditions [2,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%